Sentido De Vida En La Tercera Edad: Experiencia En Los Talleres De UPAMI En La Universidad De Flores - Stecconi, Cristina (European Scientific Journal, ESJ, 2016)
We are faced with a new demographic fact: the extension of age, and simultaneously, the increase of the quality of life of people. Regarding the expectative of life, it grew from 48 years in 1900, to 80 for women and 72 for men, in the present. Argentina and, in particular, the City of Buenos Aires, has the more â€œagedâ€ demographic profile in Latin America, along with Cuba and Uruguay. Therefore, all issues concerning the elderly and the possibility of finding meaning in life based on the occupation, are and will continue to deepen in the future. Flores University and other universities in Buenos Aires, based on an agreement with PAMI (Comprehensive Medical Assistance Program), created the UPAMI or University program, providing a specific space for elders in order to promote their personal growth, improve their quality of life and affirm the equality of opportunities for the development of cultural and vocational values. The Multiple Intelligences Questionnaire, as well and the Diagram of Behavior Areas and Fundamental Roles , both created by R. KertÃ©sz are essential for working with older adults, to find their sense of life.